Anurans (Amphibia: Anura) of the Brazilian state of Amapá, eastern Amazonia: species diversity and knowledge gaps - Taucce, Pedro P.G.; Costa-Campos, Carlos Eduardo; Carvalho, Thiago R.; Michalski, Fernanda (European Journal of Taxonomy, 2022)
We herein present the first annotated anuran checklist for the Brazilian state of Amapá, eastern Amazonia, based on a thorough literature review. We recorded the occurrence of 111 species belonging to 13 anuran families distributed across 48 localities throughout Amapá, within two biomes. Among these species, 62.5% occur exclusively in the Tropical Moist Broadleaf Forest biome, ~8% occur exclusively in the Tropical Savanna biome, and ~29% occur in both. Two species were considered endemic to Amapá and were registered only in the central portion of the state. Regarding the conservation status, only one species (Dendropsophus amicorum) is classified as threatened, assigned to the “critically endangered” category. The other species are categorized as either “least concern” or “data deficient” (85 and 8, respectively), whereas 21 are not evaluated. The current annotated list contributes to the incipient knowledge on anuran species richness in Amapá and, despite the research regarding anuran taxonomy has considerably progressed over the past 20 years, there is still much to do. Our data highlight the need for trained taxonomists to develop research in the state.